2016
DOI: 10.1002/2015ja022280
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric F2 region perturbed by the 25 April 2015 Nepal earthquake

Abstract: Seismic waves can be detected in the Earth's atmosphere and ionosphere; however, their impacts on ionospheric electron density (Ne) structures near the altitude of peak Ne (hmF2) have not yet been fully determined due to the lack of sufficient observations sampled in the vertical direction. Here we apply a ground‐based Global Positioning System (GPS) receiving network in Asia as well as the space‐based GPS occultation experiment on board the FORMOSAT‐3/COSMIC (F3/C) satellite to vertically scan the ionospheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…It is well known that an acoustic shock wave forms ahead if an object moves faster than the local sound speed. The sound speed ranges from 600 m/s to 800 m/s at the F region of ionosphere (Liu et al, ; Sun et al, ; Figure S1). A detailed description of the computation of the sound speed from the NRLMSISE00‐simulated neutral temperature and density (Picone et al, ) can be found in Figure S1 of the supporting information.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that an acoustic shock wave forms ahead if an object moves faster than the local sound speed. The sound speed ranges from 600 m/s to 800 m/s at the F region of ionosphere (Liu et al, ; Sun et al, ; Figure S1). A detailed description of the computation of the sound speed from the NRLMSISE00‐simulated neutral temperature and density (Picone et al, ) can be found in Figure S1 of the supporting information.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the vertical electron density profile from COSMIC radio occultation observations has captured the induced ion density perturbations around 300 to 440 km altitudes. Sun et al () have attributed the observed changes in RO profile to rapid uplift of F 2 layer peak altitude. On the contrary, we have shown that the observed ion density perturbations in the RO profile are mainly due to the horizontal progression of occultation (tangent) point through the positive and negative phases of southward propagating CTID as demonstrated in Figure .…”
Section: Discussionmentioning
confidence: 98%
“…Sun et al (2016) have investigated the ionospheric density perturbation induced by 25 April 2015 Nepal earthquake using FORMOSAT-3/COSMIC (F3/C) and suggested that ionospheric density is perturbed by quake induced acoustic wave speed of 800 m/s near peak altitude (hmF2). These results were in agreement with theoretical pressure oscillations.…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 99%